Business Model Development For Fashion Batik Accessories of Nyai (The Indonesian Journal of Business Administration, 2015)
Abstract. The purpose of this research is to propose a new business strategy and business model canvas model for Nyai business. Nyai is a fashion batik accessories company which focuses on offering unique products to win in the competitive fashion industry. In order to achieve that goal, Nyai should create a distinctive uniqueness, find channels to deliver the uniqueness, and formulate strategies to organize itself into intense competition in the industry. The result of this research shows that Nyai should improve its performance on quality, model, price, and brand. These variables are considered the most important for customers in purchasing fashion accessories. The diamond strategy wills facilitate a complete checklist for Nyai to conduct the improvement process.Keywords: Business Strategy, Analytical Hierarchy Process (AHP), Diamond Strategy, Fashion, Business Model Canvas